Non-English Department Students’ Perceptions of the Use of Machine Translation in Learning English - Kurniawati, Lemmuela Alvita; Clarisa, Widia (JELLT (Journal of English Language and Language Teaching), 2025)
This current study aims to investigate how non-English department students use Machine Translation (MT) to learn English and to explore the students’ perceptions of using MT to learn English. This study employed mixed methods to obtain the data by distributing online questionnaires and interviews. Involving 80 non-English department students throughout Indonesia as the participants, this study found that students use MT to translate texts from Indonesian to English and vice versa, look up the meanings of English vocabulary, phrases, and sentences, and learn how to spell and pronounce unfamiliar words. The findings also showed that the students perceived the use of MT positively, highlighting that MT is relatively easy to use, MT enhance their language learning skills, and MT has positive effects on their language learning process. The findings provide implications and future research.